Lack of genotoxicity induced by endogenous and synthetic female sex hormones in peripheral blood cells detected by alkaline Comet assay - Braz, Mariana Gobbo [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Wiley-Blackwell, 2007)
The etiology of hormone-induced cancers has been considered to be a combination of genotoxic and epigenetic events. Currently, the Comet assay is widely used for detecting genotoxicity because it is relatively simple, sensitive, and capable of detecting various kinds of DNA damage. The present study evaluates the genotoxic potential of endogenous and synthetic sex hormones, as detected by the Comet assay. Blood cells were obtained from 12 nonsmoking and 12 smoking women with regular menstrual cycles and from 12 nonsmoking women taking low-dose oral contraceptives (OC). Peripheral blood samples were collected at three phases of the menstrual cycle (early follicular, mean follicular, and luteal phases), or at three different moments of oral contraceptive intake. Three blood samples were also collected from 12 healthy nonsmoking men, at the same time as oral contraceptive users. Results showed no significant difference in the level of DNA damage among the three moments of the menstrual cycle either in nonsmoking and smoking women, or between them. No significant difference in DNA damage was also observed among oral contraceptive users, nonusers, and men. Together, these data indicate lack of genotoxicity induced by the physiological level of the female sex hormones and OC as assessed by the alkaline Comet assay. In conclusion, normal fluctuation in endogenous sex hormones and use of low-doses of oral contraceptive should not interfere with Comet assay data when this technique is used for human biomonitoring.
Keywords: Comet assay; female sex hormones; genotoxicity; oral contraceptives